History of Science (2015)
History of science is one of the reference disciplines in science education research and practice. Science education and the history of science have a long record of interactions, based on the role that history has consistently played in the narratives of science and its teaching. But, in addition, they have lived convergent developments in their making as modern academic disciplines from the 1960s to the present. A good illustration of this special relationship is the large impact that, in the last half century, Thomas S. Kuhn’s The Structure of Scientific Revolutionshas had on both fields. But the lives of history of science within science education are not restricted by the Kuhnian framework.